ANTESEDEN PERCEIVED RISK PADA PURCHASE INTENTION - Dewi Sri Rejeki (Jurnal Manajemen dan Pemasaran Jasa, 2018)
The purpose of this study is to determine the influence of perceived risk to purchase intention  private label products in Indonesia modern market. This study used primary data sources obtained directly by distributing questionnaires using purposive sampling techniques, gathered 200 respondents with minimum criteria of period at least 18 years while maximum of period is > 61 years and have bought private label products. The dependent variable in this study is purchase intention, while independent variables are considered functional risk, perceived financial risk, physical risk, and perception of psychological risk. Data analysis use Structural Equation Modeling (SEM). The results indicate that there was a negative effect on financial risk, the perceived physical risk to buy an interest in functional perception, the psychological risk has no effect on purchase intention on private label product. The implications for the manager is to increase consumer buying intentions by taking into account factors such as perceptions of financial risk and perceptions of physical risk.